Hangman’s Fracture – A Case Report and Review of Literature (Mugda Medical College Journal, 2026)
Hangman’s fractures are bilateral fractures of the C2 pars interarticularis produced during hyperextension injuries. C2 fractures are the most common form of cervical spine injury. A patient was admitted with the complaints of weakness of the left upper and lower limb following a road traffic accident. His face was spared. CT scan of the cervical spine showed bilateral pars fracture with a broken fragment. He was treated by anterior cervical fusion with tricortical bone graft and fixation between C2 and C3 with plate and screws, in the third day following trauma. The patient had immediate improvement following surgery. His weakness completely recovered and he came to follow up after one month walking without support. The anterior approach to the Hangman’s fracture is a very effective and easy procedure. Autologous tricortical bone graft gives strength as well as good fusion to the spinal column. However, careful patient selection is necessary for this. The outcome is very much rewarding to the patient.Mugda Med Coll J. 2026; 9(1): 87-91